A Critical Discourse Analysis of English Media Texts on Climate Change. M.A. Thesis Linguistics: 62 22 15 01 - Lưu, Thị Kim Nhung (ĐHNN, 2017)
This study critically analyz ed how the power relation between the developed and developing countries a s well as the ideologies about these countries ‘ responsibilities for climate change were discursively constructed in The Independent and The New York Times‟ coverage of the Conferences of the Parties to the UNFCCC between 2004 and 2013. The method of analysis was a qualitative critical discourse analysis with the support of corpus techniq ues. The findings from the study showed that although the altering but consistent ideologies were struggling with each other, they were all importan t . Th r ee main ideologies were decoded in response to the research questions . First, both unity and conflict existed in the power relation between the developed and developing countries at the global climate conferences , with the heavier weight on the conflict. Second, t he developed countries seemed reluctant and indifferent towards their responsibility for clima te change . Third, t he developing countries were required to take responsibility for climate change due to their rapid growth but they still demanded aid from the developed countries . Consequen tl y , no consensus c ould be reached on a common framework for cli mate change, and the lengthy process of global climate conference s yielded nothing but confusion and delayed action. The linguistic features of l exical choice, lexical relation, metaphor, passivization , nominalization and modality we re found ideologically invested in the newspapers‘ portrayal of the power relation and ideologies. Also, the ideologies and the language features that convey ed these ideologies we re influenced by the two media outlets‘ political commitments, news values, news agenda, and the so cio - economic and historical background that embedded the discourse . A ll in all , the media bolster ed the asymmetrical power nexus and the ideologies about the responsibilities for climate change in the interest of the developed nations.